Calcium-induced skim milk gels: Impact of holding temperature and ionic strength. (May 2020) - Lin, L.; Wong, M.; Deeth, H.C.; Oh, H.E.
Abstract: The effects of holding temperature and ionic strength on the physicochemical and rheological properties of calcium-added skim milk were investigated. In skim milk with 10–20 mmol L −1 of added calcium chloride, increasing the temperature from 20 to 53 °C decreased the calcium ion activity and pH, but increased the particle size. Increasing the holding temperature from 70 to 90 °C increased the final G′ of skim milk gels with 10–40 mmol L −1 of added calcium chloride. No gelation was observed when calcium chloride was replaced with sodium chloride to the equivalent ionic strength (60–120 mmol L −1 ). Furthermore, adding sodium chloride in addition to calcium chloride resulted in lower final G′ . The results showed that the gel strength of calcium-induced skim milk gels was influenced by holding temperature, and the effect of ionic strength was dependent on the type of salt added (Ca 2+ or Na + ).